2016
DOI: 10.1136/medethics-2016-103405
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the practice of physician-assisted dying: perceptions of physicians who had experience with complex cases

Abstract: The perceived developments could make physicians less willing to consider a request for EAS. Our results also raise questions about the role of physicians and of EAS in society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 9 publications
(5 reference statements)
1
31
0
Order By: Relevance
“…It also has been reported previously that both male and female physicians were at higher risk of suicide than gender‐matched others, and, as in nursing, female physicians were at higher relative risk than male physicians (Schernhammer & Colditz, ). More recently, though, an English study demonstrated that the risk for suicide was only higher in female physicians and nurses and not males (Snijdewind et al, ). In a possibly related finding, we did find in the open‐ended comments that the challenge of balancing home life and parenting with career demands resulted in symptomatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been reported previously that both male and female physicians were at higher risk of suicide than gender‐matched others, and, as in nursing, female physicians were at higher relative risk than male physicians (Schernhammer & Colditz, ). More recently, though, an English study demonstrated that the risk for suicide was only higher in female physicians and nurses and not males (Snijdewind et al, ). In a possibly related finding, we did find in the open‐ended comments that the challenge of balancing home life and parenting with career demands resulted in symptomatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding professional autonomy, there is a consensus that no clinician is morally obligated to participate in hastened-death. 65,74 This generally accepted ethical principle is not without its challenges. Ideally, patients seeking hastened-death would do so within the confines of a wellestablished relationship with their physician founded on mutual trust.…”
Section: Autonomy Trust and Controlmentioning
confidence: 99%
“…21,63 The evolution of hastened-death practices in Europe, where nonvoluntary euthanasia is reportedly practiced and terminal illness is not a requirement, provides a basis for those concerns. 5,7,12,73,74,99 In the Netherlands, there are reported cases where regulations were circumvented. 32 Euthanasia for psychological suffering is legal in Belgium and the Netherlands.…”
Section: Fairness Justice and Vulnerabilitymentioning
confidence: 99%
“…A broadening of the practice of euthanasia to new categories of patients may be a beneficial development, but one can be concerned with overshoot risks of instrumentalisation of physicians 36. However, integral PC nowhere implies that euthanasia is always right for every patient.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%